Price reversal as potential expiration day effect of stock and index futures: evidence from Warsaw Stock Exchange - Suliga, Milena (Managerial Economics, 2018)
This paper studies an impact of futures expiration days on the Polish equity market. From three potential expiration effects appearing in the literature (namely, the increased trading volume of underlying assets, increased volatility of their returns, and price reversal after expiration), the latest one is researched in detail for expiration days of futures on the WIG20 index, the mWIG40 index, and individual stocks. The data covers the period from January 2001 to December 2016. The phenomenon of price reversal is studied with the use of regression models, price reversal measures, and event study methodology. The results obtained for expiration days are compared with the results from non-expiration days to check whether potential price reversal can be interpreted as an effect of expiration. No price reversals after futures expirations were found in the returns of the WIG20 nor mWIG40 indexes. In the case of individual stocks, results from all of the three methods support the assumption that price reversal occurs after expiration. The reversal is immediate and is reflected inovernight returns more than in daily returns.